HANDBOOK OF INFORMATION SECURITY:KEY CONCEPTS,INFRASTRUCTURE,STANDARDS,AND PROTOCOLS - BIDGOLI,HOSSEIN (JOHN WIELY & SONS NEW JERSY,USA, 2006)
THIS BOOK IS A SET OF 3 VOLUMES WHERE EACH VOLUMES DISCUSS WITH DIFFERENT ASPECTS OF INFORMATION RATHER COMPUTER SECURITY. THIS BOOK BOOK ITSELF IS OF GREAT VALUE FROM SECURITY POINT.THIS VOL DEALS WITH OVERALL INFRASTRUCTURE OF INFORMATION SECURITY.
COMPUTER SECURITY
Keywords: COMPUTER SECURITRY,INFORMATION,PROTOCOLS